Viability test of halotolerant nitrogen-fixing rhizobacteria on different carrier composition and application dosage of nitrogen biofertilizer to increase rice growth on saline ecosystems - Fiqriah Hanum Khumairah; Fachruddin Azwari; Mieke Rochimi Setiawati; Betty Natalie Fitriatin; Tualar Simarmata (Kultivasi, 2022)
Abstract The use of saline soils as productive agricultural land poses major challenges. The utilization of nitrogen biofertilizer with halotolerant N-fixing rhizobacteria as the active material at the right dosage can increase soil productivity and support plant growth. The aim of this study was to obtain the composition of the carrier material that can maintain rhizobacteria viability, water content, and pH of nitrogen biofertilizer and to obtain the right dosage to increase the growth of rice plants in saline ecosystems. The research location was at Microbiology Laboratory of CV Bintang Asri Arthauly, Bandung and greenhouse of Jayamukti Village, Banyusari District, Karawang Regency from February to November 2020 used completely randomized design. The viability test consisted of nine treatments, while the application dosage test consisted of 13 treatments and repeated three times. The result showed that the H carrier composition (50% peat + 17.5% compost + 17.5% biochar + 5% dolomite + 5% guano + 5% nutrition) was able to maintain high viability of halotolerant N-fixing rhizobacteria compared to other treatments (10.22 x 107 CFU mL-1). Water content (34.50%) and pH level (7.9) in the composition H also meet the quality standard requirements of the biofertilizer, respectively. Nitrogen biofertilizer with H carrier composition at a dosage of 1500 g ha-1 applied to seed and nursery can increase the height and biomass of rice plants grown under saline condition. Further research is needed on the application of nitrogen biofertilizers in saline soil that can increase the effectiveness of N fertilization.Keywords: Carrier ∙ Rhizobacteria ∙ Rice ∙ Saline ecosystem ∙ Viability  AbstrakPenggunaan tanah salin sebagai lahan pertanian produktif memiliki tantangan yang besar. Pemanfaatan pupuk hayati nitrogen dengan rhizobakteri penambat N halotoleran sebagai bahan aktifnya pada dosis yang tepat dapat meningkatkan produktivitas tanah dan mendukung pertumbuhan tanaman padi. Penelitian bertujuan mendapatkan komposisi bahan pembawa yang dapat mempertahankan viabilitas rhizobakteri, kadar air, dan pH pupuk hayati nitrogen serta mendapatkan dosis yang tepat untuk meningkatkan pertumbuhan tanaman padi pada ekosistem salin. Lokasi penelitian di Laboratorium Mikrobiologi CV Bintang Asri Arthauly Bandung dan rumah kaca Desa Jayamukti, Kecamatan Banyusari, Kabupaten Karawang sejak bulan Februari sampai November 2020. Metode percobaan menggunakan metode eksperimental dengan Rancangan Acak Lengkap. Uji viabilitas terdiri dari sembilan perlakuan, sedangkan uji dosis aplikasi pupuk hayati terdiri dari 13 perlakuan dan masing-masing diulang sebanyak tiga kali. Hasil menunjukkan bahwa komposisi bahan pembawa H (Gambut  50% + kompos 17.5% + biochar 17.5% + dolomit 5% + guano 5% + nutrisi 5%) mampu mempertahankan viabilitas rhizobakteri penambat N halotoleran yang tinggi dibandingkan perlakuan lainnya yaitu sebesar 10,22 x 107 CFU/mL. Kadar air dan pH level pada komposisi H  juga memenuhi syarat baku mutu pupuk hayati yaitu sebesar 34.50% dan 7.9. Pupuk hayati dengan komposisi bahan pembawa H dengan dosis 1500 g ha-1 yang diaplikasikan pada benih dan persemaian mampu meningkatkan tinggi dan biomassa tanaman padi yang ditanam pada kondisi salin. Perlu penelitian lebih lanjut mengenai aplikasi pupuk hayati N di tanah salin yang dapat meningkatkan efektivitas pemupukan N. Kata Kunci: Bahan pembawa ∙ Ekosistem salin ∙ Padi ∙ Rhizobakteria ∙ Viabilitas